Studies on Modeling and Physicochemical Properties of Oil Extracted from Moringa stenopetala Seed - Lema Deme Shumi; Ebise Getacho Bacha (Advances in Materials Science and Engineering)
Moringa stenopetala, locally known as Shiferraw, is an indigenous vegetable tree native to southern Ethiopia and grown mainly for its food value. This study deals with the investigations of physicochemical characteristics of Moringa stenopetala seeds’ oil extracted using solvent extraction with food-grade hexane as a solvent and Analysis of Variance (ANOVA) of the extraction parameters. The seeds were collected from Adama located in Oromia, East Shewa Zone of Ethiopia, and they exhibit the average moisture, ash, fiber, protein, and oil contents of 6.3, 4.2, 2.3, 27.5, and 40.2%, respectively. Temperature, extraction time, and particle size had a significant p<0.05 effect on the oil yield. According to the Experimental Design Response Surface Methodology (RSM) and ANOVA analysis, the optimum process parameters’ combination to find the highest oil yield was particle size of 0.83 mm, the temperature at 78.82°C, and extraction time of 5.13 hours. The model predicted oil yield was 39.7 ± 0.32%. The oil from Moringa stenopetala seed exhibits physiochemical characteristics of refractive index (40°C), 1.4625; viscosity 49.4 Cp; density at 25 °C, 0.9317 g/cm−3; saponification value, 191.4; peroxide value, 11.52 millieq O2/kg; iodine value of 89.21; and Acid Value (AV) 2.21 mg KOH/g. Fourier-transform infrared spectroscopy (FT-IR) analysis shows that the oil contains both ester carbonyl (C=O) functional groups saturated and unsaturated fatty acid. The physicochemical properties of Moringa stenopetala seeds were compared with other edible oil properties such as sesame, groundnut, olive, and sunflower seeds. The result shows that in the future Moringa stenopetala could be used as a substitute for other oil-bearing seeds sources, such as soybean, sunflower, and groundnut.